Policy design and public support for carbon tax: Evidence from a 2018 US national online survey experiment. (6th July 2020) - Dolšak, Nives; Adolph, Christopher; Prakash, Aseem
Abstract: Public support for policy instruments is influenced by perceptions of how benefits and costs are distributed across various groups. We examine different carbon tax designs outlining different ways to distribute tax revenues. Using a national online sample of 1, 606 US respondents, we examine support for a 20/ton carbon tax that is: (1) revenue neutral: revenue is returned to citizens via tax cuts; (2) compensation‐focused: revenue is directed to helping actors disproportionately hurt by the tax; (3) mitigation‐focused: revenue funds projects reducing carbon emissions; and (4) adaptation‐focused: revenue is directed to enhancing community resilience to extreme weather events. We find devoting revenue to mitigation raises overall support for carbon tax by 6.3 per cent versus the control (54.9 per cent) where no information on spending is provided. Other frames raise support in specific subgroups only. Revenue neutrality raises support among lower‐income households (+6.6 per cent) and political independents (+9.4 per cent), while compensation increases support among lower‐income repondents (+6.1 per cent).